Female-Programmer in Education and Career: Technofeminism Studies in Science and Technology - Pratiwi, Andi Misbahul (Jurnal Perempuan, 2016)
This paper defines womenâ€™s status and agency in Information Technology (IT) in education and career as a programmer. In fact, technology is never a neutral ground. Technologies have a masculine image not only because they are dominated by men but because they incorporate symbols, metaphors and values that have masculine connotations. How do women define, control and transform herself in this area? The transformation of relationship between women and machine is important to be investigated. The new definition about masculinity domination and the new style is the technofeminism movement. Technofeminist approachesemphasize that the genderâ€“technology relationship is fluid and flexible. Therefore we can re-define â€œtechnophobiaâ€ to â€œtechnophiliaâ€, as a celebration of womanâ€™s agency to new digital age.